Pendidikan Sebagai Pembelajaran Dan Pemberadaban: Belajar Dari Drijarkara - Alois A. Nugroho (Respons: Jurnal Etika Sosial, 2016)
Character building is the focal point in Driyarkara’s philosophy of education. He has published his thought in various forms of writing and speech. Sukarno did the same thing about education as the process of nation and character building. Both Drijarkara and Sukarno underlined in their thoughts and speeches the wholeness of man in his/her culture which is now facing globalization as “the runaway world”. For this reason, development of a nation-state must be directed to strengthen people’s national identity.Education, character building, nation building, national identity, and integration.Pendidikan watak atau pendidikan kepribadian merupakan fokus pemikiran Drijarkara tentang pendidikan. Ia sudah menampilkan pemikiran tersebut dalam berbagai tulisan dan pembicaraan. Sukarno membicarakan pendidikan watak yang dianggapnya penting untuk membentuk rasa berbangsa dan bernegara. Demikian halnya Drijarkara, ia membicarakan pendidikan watak dengan memberi penekanan pada keutuhan manusia dalam budayanya menghadapi globalisasi. Atas dasar itulah pembangunan negara-bangsa diarahkan kepada penguatan identitas nasional manusia.Pendidikan, pembentukan watak, pembentukan rasa kebangsaan, dan integrasi